New fossil Prophalangopsidae (Orthoptera, Hagloidea) from the Middle Jurassic of Inner Mongolia, China - Gu, Junjie; Zhao, Yun-Yun; Ren, Dong (Zootaxa, 2009)
Two new species attributed to the genus Sigmaboilus Fang, Zhang & Wang, 2007 are described from the Middle Jurassic Jiulongshan Formation of Daohugou Village, Inner Mongolia, China: Sigmaboilus fuscus sp. nov., S. peregrinus sp. nov. The diagnosis of the genus is revised.